Scaling of deterministic lateral displacement devices to a single column of bumping obstacles. Issue 18 (17th August 2020) - Liang, Weibin; Austin, Robert H.; Sturm, James C.
Abstract : Scaling DLD array devices to a single column of bumping obstacles to increase throughput per area and minimize device area. Abstract : We describe a deterministic lateral displacement (DLD) for particle separation with only a single column of bumping features. The bifurcation of fluid streams at obstacles is not set by the "tilt" of columns with respect to macroscopic current flow, but rather by the fluidic resistances for lateral flow at each obstacle. With one column of 14 bumping features and corresponding inlet/outlet channels, the single-column DLD can separate particles with diameters of 4.8 μm and 9.9 μm at 30 μL min −1, with an area of only 0.37 mm × 1.5 mm (0.55 mm 2 ). The large-cell output contains over 99% of the 9.9 μm particles and only 0.2% of the 4.8 m particles. The throughput per area of 54 μL min −1 per mm 2 represents a 10× increase over previous selective harvesting reports for microfluidic devices in a similar particle size range.